2003
DOI: 10.1029/2002jd002513
|View full text |Cite
|
Sign up to set email alerts
|

Mixing states of individual aerosol particles in spring Arctic troposphere during ASTAR 2000 campaign

Abstract: The present study mainly focuses on the mixing states of aerosol constituents and their vertical distribution in spring Arctic troposphere during the ASTAR 2000 campaign (T. Yamanouchi et al., Arctic Study of Tropospheric Aerosol and Radiation (ASTAR) campaign: An overview and first results, submitted to Bulletin of the American Meteorological Society, 2002) (hereinafter referred to as Yamanouchi et al., submitted manuscript, 2002). Sulfate and soot were identified as major aerosol under both Arctic haze and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
56
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 59 publications
(78 reference statements)
8
56
2
Order By: Relevance
“…The proportion of particles containing internally mixed soot is higher than that reported by Okada et al (2005) for Australia, Hara et al (2003) for the Arctic, and Hasegawa and Ohta (2002) for Japan and Alaska, even though most of our MC samples were less aged. Since our MC samples were collected close to their sources, generally within less than eight hours after emission and yet were coated when collected, we conclude that the rate of coating was rapid, consistent with the results of Doran et al (2007), Johnson et al (2005), and Baumgardner et al (2007).…”
Section: Om-s Coatings On Soot Particlescontrasting
confidence: 39%
“…The proportion of particles containing internally mixed soot is higher than that reported by Okada et al (2005) for Australia, Hara et al (2003) for the Arctic, and Hasegawa and Ohta (2002) for Japan and Alaska, even though most of our MC samples were less aged. Since our MC samples were collected close to their sources, generally within less than eight hours after emission and yet were coated when collected, we conclude that the rate of coating was rapid, consistent with the results of Doran et al (2007), Johnson et al (2005), and Baumgardner et al (2007).…”
Section: Om-s Coatings On Soot Particlescontrasting
confidence: 39%
“…for estimating the aerosol mass mixing ratio). The main results of the entire airborne impactor measurements have already been discussed in detail in Hara et al (2002Hara et al ( , 2003. The findings for 23 and 26 March are as follows: the main components were sulfate, soot and sea salt particles; smaller components include a small number of mineral dust particles.…”
Section: Vertical Profile From Airborne Observationsmentioning
confidence: 75%
“…The absorption efficiency for BC (7.3 m 2 g −1 ) is close to the recommended value of 7.5 m 2 g −1 from . In the atmosphere it is observed that BC is a combination of external and internal mixtures (Horvath, 1993;Hara et al, 2003;Wentzel et al, 2003;Mallet et al, 2004;Cheng et al, 2006). Further, it is well known that an internal mixture for BC enhances the absorption compared to an external mixture.…”
Section: Radiative Forcingmentioning
confidence: 94%